Site-Specific Protein Modifications by an Engineered Asparaginyl Endopeptidase from Viola canadensis - Chen, Yu; Zhang, Dingpeng; Zhang, Xiaohong; Wang, Zhen; Liu, Chuan-Fa; Tam, James P. (Frontiers in Chemistry, 2021)
Asparaginyl endopeptidases (AEPs) or legumains are Asn/Asp (Asx)-specific proteases that break peptide bonds, but also function as peptide asparaginyl ligases (PALs) that make peptide bonds. This ligase activity can be used for site-specific protein modifications in biochemical and biotechnological applications. Although AEPs are common, PALs are rare. We previously proposed ligase activity determinants (LADs) of these enzymes that could determine whether they catalyze formation or breakage of peptide bonds. LADs are key residues forming the S2 and S1′ substrate-binding pockets flanking the S1 active site. Here, we build on the LAD hypothesis with the engineering of ligases from proteases by mutating the S2 and S1′ pockets of VcAEP, an AEP from Viola canadensis. Wild type VcAEP yields <5% cyclic product from a linear substrate at pH 6.5, whereas the single mutants VcAEP-V238A (Vc1a) and VcAEP-Y168A (Vc1b) targeting the S2 and S1′ substrate-binding pockets yielded 34 and 61% cyclic products, respectively. The double mutant VcAEP-V238A/Y168A (Vc1c) targeting both the S2 and S1′ substrate-binding pockets yielded >90% cyclic products. Vc1c had cyclization efficiency of 917,759 M−1s−1, which is one of the fastest rates for ligases yet reported. Vc1c is useful for protein engineering applications, including labeling of DARPins and cell surface MCF-7, as well as producing cyclic protein sfGFP. Together, our work validates the importance of LADs for AEP ligase activity and provides valuable tools for site-specific modification of proteins and biologics.